2016
DOI: 10.1097/spc.0000000000000225
|View full text |Cite
|
Sign up to set email alerts
|

Withholding versus withdrawing treatment: artificial nutrition and hydration as a model

Abstract: Despite many believing that there is no ethical, medical, or moral difference between withholding and withdrawing of life-sustaining treatment, there is no denying it is emotionally taxing, particularly withdrawal of ANH. Upholding the patient's values during high-quality shared decision making, facilitating rapport, and utilizing time limited trials will help, even when treatment is considered medically ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…While ethicists argue that withdrawal and nonescalation are morally equivalent, 25 clinicians note that the cultural, psychological, social, or emotional experience of the 2 modes of death are significantly different. [26][27][28] Despite the need for family centered communication, shared decision-making, and values-oriented communication regardless of the mode of death, discussions around withdrawal of life-sustaining technologies require different knowledge and skills than discussions around nonescalation or disclosure of a failed resuscitation. 26,29 Medical management, as well as important cultural and ethical considerations, varies widely by mode of death.…”
Section: Resident Exposure To Mode Of Deathmentioning
confidence: 99%
“…While ethicists argue that withdrawal and nonescalation are morally equivalent, 25 clinicians note that the cultural, psychological, social, or emotional experience of the 2 modes of death are significantly different. [26][27][28] Despite the need for family centered communication, shared decision-making, and values-oriented communication regardless of the mode of death, discussions around withdrawal of life-sustaining technologies require different knowledge and skills than discussions around nonescalation or disclosure of a failed resuscitation. 26,29 Medical management, as well as important cultural and ethical considerations, varies widely by mode of death.…”
Section: Resident Exposure To Mode Of Deathmentioning
confidence: 99%
“…Moreover, families may have more difficulty trusting what they hear, and are more often asked to reconcile themselves to assisted hydration ceasing, rather than not starting. Although some ethicists may deny a distinction between acts and omissions, 37 participants suggested that they, patients and families find cessation of assisted hydration harder to process 38,39 ; the widely-used time-limited trial of assisted hydration is a practical solution. 40 The number and quality of hospital-based discussions about assisted hydration are unlikely to improve unless resources are less thinly stretched, and unless clinicians observe practice and receive education that engenders comfort with uncertainty and avoids dichotomous right-vs-wrong viewpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Experience of actively initiating discussions on LST withdrawal with patients' families was significantly related to LST decision discussions in this study. Withdrawing treatments is difficult and emotional for physicians and nurses, patients, and families [24,32]. Pressures on discussions about LST withdrawal may arise from patient prognosis, physician factors, nurse factors, concerns from patients' families, social factors, and economic factors [14].…”
Section: Discussionmentioning
confidence: 99%